Pengaruh Pengunyahan Permen Karet dengan Pemanis Xylitol terhadap Penurunan Risiko Karies Gigi - Wahyu Sulistiadi (Faculty of Dentistry, Universitas Indonesia, 2015)
The aim of this study was to assess the relation between the use of xylitol chewing gum and risk of dental caries. The sample was taken from a population of 800 (120 samples). Standard equipment was used in observing the dental plaque, salivary flow rate and pH of the saliva from patients using xylitol chewing gum or non xylitol chewing gum. The results were analyzed using the t-test (one tailed) with 95% confidence intervals (α ≤ 0.05). The results show a significant effect of chewed xylitol gum with increased pH in saliva, increased salivary flow rate (SFR), and decreased plaque score.